On and Off Farm Crop Residue Management: A brief review on Options, Benefits, Drawbacks, Limitations and Policy Interventions - Singh, Deepti; Mina, Usha (Journal of Cereal Research, 2022)
India ranks as second largest country for agro-based economy having about 1.79 MKM2 agricultural land that generates approximately 686 Million Tonnes (MT) of gross crop residues including approximately 234 MT surplus residues annually. In 686 MT crop residue, contribution of crop types as well as states is variable. In the present study, the role of crop residue as an important natural and renewable resource along with their on and off farm management options having their own benefits, drawbacks and limitations were discussed. Various terminologies used for crops’ residue and methodoloies used to estimate their generation potential were analysed. Different factors regulating the crop residue usage for diverse purposes which affects their end use were identified and listed. As, raw and condensed form of crop residues have different physico-chemical properties and resource value. Various on and off farm crop residue management options including crop residue burning, residue removal, residue retention, residue incorporation, composting, biochar production, livestock feed, mushroom cultivation, biofuel biogas and bioenergy production from different crop residues were compared. Various Government initiatives to minimise and support the unsustainable and sustainable crop residue management options, respectively were reviewed